Rapid diagnosis of non-tuberculous mycobacterial pulmonary diseases by metagenomic next-generation sequencing in non-referral hospitals - Wang, Jing; Xu, Huan; Wang, Xi; Lan, Jian (Frontiers in Cellular and Infection Microbiology, 2023)
The incidence of nontuberculous mycobacterial pulmonary disease (NTM-PD) increases steadily globally, but the current culture-based diagnosis of NTM-PD is difficult and time-consuming, leading to a high possibility of missed diagnosis. Thus, new methods should be introduced to improve the clinical diagnosis. Our retrospective observational study enrolled 12 NTM-PD patients with the assistance of mNGS as well as the characteristic radiological presentation of slowly progressed, usually concomitant of bronchiectasis, small cavitary opacity and multiple nodules which respond poorly to empirical antibiotic therapy. These patients received the recommended drug regimen based on the identified NTM species. Clinical data, including symptoms, laboratory tests, dynamic computed tomography imaging, treatment, and outcome, were recorded and analyzed. The results of mNGS were all positive, with standard specifically mapped read number (SDSMRN) of NTM varying from 1 to 766, which confirmed in six patients by qPCR. Duration from sample collection to mNGS results was 1 to 3 days. Among our 12 patients, except for 1 patient was lost to follow-up, all the remaining 11 patients showed significant absorption of lesion on CT imaging. Our results draw attention to NTM infection as a possible cause of community acquired pneumonia, especially in patients with suggestive radiological presentation and poor responses to empirical antibiotic therapy. Our study also indicated that mNGS represents a potentially effective tool for the rapid identification NTM in the respiratory sample. The improved clinicians’ awareness combined with the utilization of mNGS could guide earlier diagnosis and targeted treatment, and improve the prognosis of patients with NTM-PD.